Divine Justice and Gender Equity in Islam: A Qur’anic Analysis of Inheritance and Women’s Testimony - Zubaidi, Sujiat; Arifah, Farah Nur; Sansayto, Ide Mafaza (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2025)
This study investigates the Qur’anic concept of divine justice as it relates to inheritance distribution and the role of women in legal testimony, areas often debated for their gender-specific rulings. While these provisions may appear to privilege men, this research explores the underlying rationale that integrates social roles, economic responsibilities, and ethical principles within Islamic jurisprudence. According to Islamic teachings, the objective is to elucidate how these distinct legal norms contribute to a balanced and just society. Employing a Qur’anic semantic analysis, the study focuses on key verses from Surah ’Al-Nisā’ [4]: 11 , 176 and Surah Al-Baqarah [2]:282, supplemented by classical and contemporary interpretations and the maqāṣid al-shariah framework emphasising justice and social harmony. Findings reveal that the Qur’anic guidance aims to establish justice by recognizing equality in dignity while differentiating rights and duties based on social and financial roles. For example, the unequal inheritance shares reflect men’s broader financial obligations to family stability, and testimony rules prioritise evidentiary reliability over gender bias. The study concludes that the Qur’anic justice model balances individual rights with collective responsibilities, fostering social cohesion and challenging simplistic views of discrimination. This research contributes to scholarly discourse by clarifying the ethical and jurisprudence foundations of gender-specific legal provisions in Islam.